ANALYSIS OF DEFORMATION PROCESSES IN THE LITHOSPHERE FROM GEODETIC MEASUREMENTS BASED ON THE EXAMPLE OF THE SAN ANDREAS FAULT - Yury V. Gabsatarov (Геодинамика и тектонофизика)
Analysis of data from permanent GPS observation stations located in tectonically active regions provides for direct observation of deformation processes of the earth's surface which result from elastic interaction of the lithospheric plates and also occur when accumulated stresses are released by seismic events and postseismic processes.This article describes the methodology of applying the regression analysis of time series of data from GPS-stations for identification of individual components of the stations’ displacements caused by the influence of various deformation processes. Modelling of the stations’ displacements caused only by deformations of the marginal zone, wherein the lithospheric plates interact, allows us to study variations of the steady-state deformation in the marginal zone.he proposed methodology is applied to studies of variations of fields of cumulative surface displacements, surface displacement velocity and maximum shear strain velocity which are determined from the GPS data recorded prior to the Parkfield earthquake of 28 September 2004 (Mw=6.0).Combined analysis of the variations of the above-mentioned fields shows that measurable anomalies of the elastic deformation of the transform fault’s edge took place prior to the seismic event of 28 September 2004, and such anomalies were coincident in space and time with the focal area of the future seismic event.